2003
DOI: 10.1038/sj.ijo.0802254
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the treatment of obesity: a review of the evidence

Abstract: Although acupuncture is being utilized to treat a variety of important health problems, its usefulness in obesity management has not yet been fully evaluated. The aim of this review paper was to survey and critically evaluate the descriptive and controlled trials of acupuncture for enhancing weight loss. The underlying principles of acupoint stimulation are described, with an emphasis on auricular (ear) acupuncture, the method most often chosen for obesity studies. The difficulties of selecting suitable placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(73 citation statements)
references
References 47 publications
2
62
0
7
Order By: Relevance
“…8,9 Despite the above results, the effectiveness of acupuncture on obesity has not been fully understood. Lacey et al 10 reviewed seven randomized controlled trials (RCTs) and reported a modest positive effect of acupuncture for weight loss, although his review was nonsystematic. Meanwhile, Ernst 11 reported an inconclusive result regarding the efficacy of acupuncture on weight loss based on a systematic review, but without a meta-analysis, of four RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Despite the above results, the effectiveness of acupuncture on obesity has not been fully understood. Lacey et al 10 reviewed seven randomized controlled trials (RCTs) and reported a modest positive effect of acupuncture for weight loss, although his review was nonsystematic. Meanwhile, Ernst 11 reported an inconclusive result regarding the efficacy of acupuncture on weight loss based on a systematic review, but without a meta-analysis, of four RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,21,22 However its role in obesity control remains largely controversial. [11][12][13] Animal experiments suggest that acupuncture may reduce the appetite with the regulation of feed-related lateral hypothalamic (feeding center) and ventromedial hypothalamic (satiety center) neuronal activity. 23 Despite the minimal side effects, we found some interesting phenomena in our study groups, including the improvement of constipation (two patients) and dysmenorrhea (three patients).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Acupuncture is being utilized to treat a variety of health problems, one of which is obesity management. 11 However, the majority of reports lack a well-controlled design. 11,12 Thus, we conducted this randomized crossover clinical trial to examine its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Such moderating variables may obscure real differences between groups especially in small samples. One suggested mechanism to control for patients' expectations is the treatment credibility assessment, adapted from Borkovec and Nau (Lacey et al, 2003, as cited in Borkovec & Nau, 1982, which is a simple series of four questions designed to measure the individual's belief www.intechopen.com in the efficacy of treatment. Ideally, the mean scale scores should be equivalent for both treatment and control groups to ensure that the groups are comparable.…”
Section: Reflection About Acupuncture Weight Loss Research Approachmentioning
confidence: 99%
“…Standard algorithms need to be developed, based on principles used by practitioners, for example, criteria for selecting and changing point locations, and spacing of treatments (Lacey et al, 2003).…”
Section: Reflection About Acupuncture Weight Loss Research Approachmentioning
confidence: 99%